Association of non-scarring alopecia and vitamin D levels: A case control study - Saqib, Zareen; Kiran, Rutaba; Rana, Mahwash; Khan, Sadaf Naveed; Seemi, Hafiza Sidra; Rani, Zahida; Khan, Ayaz (Journal of Pakistan Association of Dermatologists, 2024)
Objective To determine the association between non scarring alopecia and vitamin D levels. Â Methods 69 patients with non-scarring alopecia and 69 age matched controls were enrolled in the study using non purposive consecutive sampling, after taking informed consent. Serum vitamin D and haemoglobin levels were determined and compared for both groups. Â Results The mean age of the case group was 26.35Â±8.96 years while that of the control was 31.36Â±9.6 years. 93% cases and 83% controls belonged to the female gender while only 17 individuals were males. There was no difference in dietary habits between the two groups, and about 15% individuals from both groups were vegetarians. The hair pull test was positive in 42% cases and 13% controls. The hemoglobin levels were comparable in both groups although about 7% cases and none of the controls had severe anemia. More than half the cases and controls had Vitamin D deficiency and almost one third had Vitamin D insufficiency with cases having a slightly lower mean Vitamin D level of 23.12Â±16.70 and controls having a mean of 23.75Â±18.63. The Chi square test for comparison of vitamin D levels between two groups has p value of 0.06 which is statistically not significant. Â Conclusion Vitamin D deficiency is frequently associated with non-scarring alopecia. Vitamin D levels should be measured as routine investigation in patients of hair loss. However, we also found comparable prevalence of vitamin D insufficiency in the control population, so we recommend food fortification with vitamin D to alleviate this problem at community level. Â